Zanclean/Piacenzian transition on Cyprus (SE Mediterranean): calcareous nannofossil evidence of sapropel formation. - Athanasiou, M.; Triantaphyllou, M.; Dimiza, M.; Gogou, A.; Τheodorou, G. (Geo-Marine Letters, 2015)
Quantitative analyses of calcareous nannofossils in the sediments of Pissouri South section on the island of Cyprus have produced a paleoceanographic record reflecting the paleoclimatic conditions during the Zanclean/Piacenzian transition. Pissouri South cyclical lithological alternations between organic-rich laminated layers and grey marls reflect the Earth’s orbital precession. According to the calcareous nannofossil biostratigraphy which has been performed, the studied section is correlated with MNN14/15 and MNN16 calcareous nannofossil biozones and is astronomically dated between 4.065 and 3.217 Ma. Intervals of increased organic carbon content, along with the positive values ofFlorisphaera profunda, Helicosphaera sellii, Discoaster spp. and the subsequent increase of stratification S-index, correspond to the sapropel deposition during periods of wetter climate and intense continental runoff, especially from the river Nile. These layers alternate with grey marly intervals, featured by the increased values of small placoliths of Reticulofenestra and Gephyrocapsaspecies, which are indicative of eutrophic conditions during intense surface-water mixing. Our data support the prevalence of a generally warm phase characterized by the absence of high-frequency climate variations in the southeastern Mediterranean during the Zanclean/Piacenzian (Early/Late Pliocene) transition.